In too deep eaudiobook - Child, Lee (Jack Reacher, 2024)
#1 NEW YORK TIMES BESTSELLER • A gripping Jack Reacher thriller from the bestselling authors Lee Child and Andrew Child Don’t miss the hit streaming series Reacher ! Reacher had no idea where he was. No idea how he had gotten there. But someone must have brought him. And shackled him. And whoever had done those things was going to rue the day. That was for damn sure. Jack Reacher wakes up alone, in the dark, handcuffed to a makeshift bed. His right arm has suffered some major damage. His few possessions are gone. He has no memory of getting there. The last thing Reacher can recall is the car he hitched a ride in getting run off the road. The driver was killed. His captors assume Reacher was the driver’s accomplice and patch up his wounds as they plan to make him talk. A plan that will backfire spectacularly . . .